Healthcare costs of urinary tract infections and genital mycotic infections among patients with type 2 diabetes mellitus initiated on canagliflozin: a retrospective cohort study. (4th March 2017) - Amos, Tony B.; Montejano, Leslie; Juneau, Paul; Bolge, Susan C.
Abstract: Objective: To assess the economic impact of urinary tract infections (UTIs) and genital mycotic infections (GMIs) among patients with type 2 diabetes mellitus (T2DM) initiated on canagliflozin. Methods: Administrative claims data from April 2013 through June 2014 MarketScan ® databases were extracted. Adults with ≥1 claim for canagliflozin, T2DM diagnosis, and ≥90 days enrollment before and after canagliflozin initiation were propensity score matched to controls with T2DM initiated on other anti-hyperglycemic agents (AHAs). UTI and GMI healthcare costs were evaluated 90-days post-index and reported as cohort means. Results: Rates of UTI claims 90 days post-index were similar in patients receiving canagliflozin for T2DM ( n = 31, 257) and matched controls (2.7% vs 2.8%, p = .677). More canagliflozin than control patients had GMI claims (1.2% vs 0.6%, p < .001) and antifungal utilization (5.3% vs 2.6%, p < .001). Mean post-index costs to treat UTIs were lower but not significantly different for canagliflozin patients vs matched controls (27.61 vs 37.33, p = .150). GMI treatment costs were higher for the canagliflozin cohort (3.68 vs 2.44, p = .041). Combined costs to treat either UTI and/or GMI averaged 31.29 per patient for the canagliflozin cohort v 39.77 for controls ( p = .211). Rates and costs of UTIs and GMIs were higher for females than males, but the canagliflozin vs control trends observed for the overall sample were similar for both sexes. There were no significant cost differences between the canagliflozin and control cohorts among patients aged 18–64. Among patients aged 65 and above, GMI treatment costs were not significantly different, but costs to treat UTIs and either UTI and/or GMI were significantly lower for canagliflozin patients vs controls. Conclusions: In a real-world setting, the costs to payers of treating UTIs and GMIs are generally similar for patients with T2DM initiated on canagliflozin vs other AHAs.